Python programming for the absolute beginner - Dawson, Michael (Clifton Park, N.Y. : Delmar ; Andover : Cengage Learning [distributor], 2009)
This title is ideal for the beginning programmer who wants to learn Python, a powerful, flexible, and concise programming language.
Keywords: Python (Computer program language); Computers and IT